Lacrimal sac rhinosporidiosis. Issue 6 (28th June 2021) - Parida, Pradipta Kumar; Thangavel, Saranya; Raja, Kalaiarasi; Saxena, Sunil Kumar
Abstract : Rhinosporidiosis is a chronic mucocutaneous granulomatous disease caused by Rhinosporidium seeberi, involving primarily the nose and nasopharynx. Very rarely, the disease can affect the lacrimal sac. Here we report a 35-year-old male patient who had rhinosporidial involvement of the nose 5 years ago, for which he underwent endoscopic nasal surgery. Five years after the excision of the nasal mass, he presented with lacrimal sac involvement. The clinical presentation and the management of lacrimal sac rhinosporidiosis are discussed here.